"Итак, моя милая..." - Чейз Джеймс Хэдли (Криминальная коллекция, 1993)
Экземпляры: КХ (20111013) / Инвентарный номер: 1011696 / Цена: 225.00 / Сис.шифр: И(Англ) / Авт.знак: Ч-36 / ГРНТИ: 17 / ББК: 84(4/8)